Practice Relativism - Stephen P. Turner (Crítica)
Practice relativism is the idea that practices are foundational for bodies of activity and thought, and differ from one another in ways that lead those who constitute the world in terms of them to incommensurable or conflicting conclusions. It is true that practices are not criticizable in any simple way because they are largely tacit and inaccessible. But to make them relativistic one needs an added claim: that practices are “normative”, or conceptual in character. It is argued that this is not supportable by any explanatory necessity, and that the differences in outcomes, though real, are not instances of relativism.